The Analysis of Swearing Word Translation in Joker Movie Subtitle - Hapni Nurliana H.D Hasibuan (Universitas Ahmad Dahlan, 2021)
This research discusses the analysis of swearing words translation in the Joker movie. The purpose of this research is to describe the type of swearing word and the procedure used in translating swearing word. This study uses qualitative methods. The research data were obtained from English subtitles to Indonesian Joker movies. To answer the research question, the researcher used the theory types of swearing word proposed by Swan M. (1995) and procedure translation proposed by Newmark (1988) The results revealed that there were 49 swearing words. There are 2 types of swearing words namely: strong and weak swearing words. For strong swear words classified to exclamation of annoyance, surprise, insult, surprise question and emphasize the emotion and the weak swear word classified to exclamation of annoyance, surprise, insult and emotion. After that, procedures translation used in translating swear words only found 5 of 15 procedure translation in Joker's subtitle, namely: cultural equivalent, synonymy, through-translation, shift or transposition, and paraphrase. The most frequently type of swearing word is emphasize an emotion from strong swear word. Furthermore, the cultural equivalent procedure is the most used in translating.